Sec4A(1-Sin4A) - 2tan2A=1
prove the following
Answers
Answered by
6
Answer:
Step-by-step explanation:
sec⁴A(1-sin⁴A)-2tan²A
=sec⁴A-sec⁴Asin⁴A-2tan²A
=sec⁴A-sin⁴A(1/cos⁴A)-2tan²A
=sec⁴A-tan⁴A-2tan²A
={(sec²A)²-(tan²A)²}-2tan²A
=(sec²A+tan²A)(sec²A-tan²A)-2tan²A
=sec²A+tan²A-2tan²A [∵, sec²A-tan²A=1]
=sec²A-tan²A
=1 (Proved)
sweety19972:
thanks
Answered by
8
Answer :
sec4A ( 1 - sin4A) - 2tan2A =
1/ COS4A (1 - sin4A) - 2tan2A
= (1/ COS4A - sin4A/ COS4A) - 2tan2A
= { ( 1 -S IN4A)/ COS4A }- 2tan2A
= { (1 - SIN2 A ) (1+SIN2 A)/ COS4A }- 2tan2A
={COS2A (1+SIN2 A)/ COS4A }- 2tan2A
= (1+SIN2 A)/ COS2A - 2S IN2A / COS2 A
=( (1+SIN2 A) - 2S IN2A) / COS2 A
= (1 - SIN2 A )/ COS2 A = COS2 A / COS2 A = 1
(1 - SIN2 A ) = COS2 A
So Cos'2A = Cos'2A
So Proved 1=1
Similar questions